(untitled) (Agricultural Engineering, 2023)
In many cases, old working mills, use machines that are several dozen years old, which are not adapted to the safety requirements. Their use may result in an accident at work. The article presents a case study of the work safety assessment in an old mill. The analysis was carried out with the use of a proprietary checklist, taking into account the current safety requirements. Non-conformities that were identified as the results of the analysis, had an impact on the level of security. The greatest number of non-conformities concerned the fulfillment of technical requirements. Actions aimed at improving work safety were proposed. The prepared checklist is a universal tool for assessing work safety in mills in Poland.